The Effect of Hypericum Perforatum Extract and 1 % Silver Sulfadiazine on Second Degree Burn Wound Healing in Male Rats - E Momeni (Armaghane Danesh Bimonthly Journal, 2014)
Backgrounds & aim: Hypericum is a traditional medicinal plant that used for the topical treatment of superficial wounds, burns and dermatitis.the aim of this study was to evaluate the effect of Hypericum perforatum extract and1 % silver sulfadiazine on a second degree burn wound healing in the male rat.